Electronic properties of single-layer CoO2/Au(111). (11th June 2021) - Holt, Ann Julie U.; Pakdel, Sahar; Rodríguez-Fernández, Jonathan; Zhang, Yu; Curcio, Davide; Sun, Zhaozong; Lacovig, Paolo; Yao, Yong-Xin; Lauritsen, Jeppe V; Lizzit, Silvano; Lanatà, Nicola; Hofmann, Philip; et al.
Abstract: We report direct measurements via angle-resolved photoemission spectroscopy (ARPES) of the electronic dispersion of single-layer (SL) CoO2 . The Fermi contour consists of a large hole pocket centered at the Γ ‾ point. To interpret the ARPES results, we use density functional theory (DFT) in combination with the multi-orbital Gutzwiller Approximation (DFT+GA), basing our calculations on crystalline structure parameters derived from x-ray photoelectron diffraction and low-energy electron diffraction. Our calculations are in good agreement with the measured dispersion. We conclude that the material is a moderately correlated metal. We also discuss substrate effects, and the influence of hydroxylation on the CoO2 SL electronic structure.